Over a million students use our free study notes to help them with their homework
Assumption: If sqrt(2^n- 1) ∈ℕ , it means that there is a k ∈ ℕ such that (2^n-1) = k^2 ⇒ k is odd, so there is m ∈ ℕ such that (2^n-1)=(2m+1)^2 . By solving the equation we get 2^n= 4m^2+4m+2. We divide...
Make x the subject in the equation x+y=11(1). This will help us eliminate x in the second equation (2).x=11-y (3)Substitute (3) into (2)(11-y)2+y2=61Expanding the brackets and simpli...
Start by finding the first derivative of the function - by differentiating f(x) with respect to x. Then substitute the x-coordinate, in this case 2, into the first derivative and it will equal zero if (2,...
Differentiation is something you can do to a function, to tell you about the gradient of the function. For your simple linear, quadratic, cubic, etc. equations, the process is the same every single time. ...
Let u = 3x4 + xdu/dx = 12x3 + 1y = u5dy/du = 5u4<...
←
103
104
105
106
107
→
Internet Safety
Payment Security
Cyber
Essentials